1977
DOI: 10.1002/hlca.19770600713
|View full text |Cite
|
Sign up to set email alerts
|

Polymergebundene Cinchonaalkaloide als Katalysatoren in der Michael Reaktion

Abstract: Polymer Bound Cinchona Alkaloids as Catalysts in the Michael Reaction SummaryThree insoluble chiral polymers (6, 7 and 8) were prepared by functionalization of copoly(styrene -2% divinyl benzene) followed by reaction with quinine (9) or dihydrocupreine (10). Their utility as catalysts, in the reaction between methyl indane-1 -one-2-carboxylate (13) and 3-butene-2-one (14) was studied. Table 2 (runs 2-6 and 8) shows that the Michael-adduct 15 was formed in good chemical but low optical yields, independent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 12 publications
0
14
0
2
Order By: Relevance
“…Immobilization of quinine alkaloids onto polymers (styrenedivinylbenzene or acrylonitrile) allows asymmetric conjugate addition of MVK to indanone derivatives, although the selectivity is dramatically diminished. [143,144] More recently, Wu et al have reported the use of cinchona alkaloids 230 for the Michael addition of several vinyl ketones to keto-esters with good yields and enantioselectivities at room temperature (however the configuration of the stereogenic center is not reported) (Scheme 62). [145] The phenanthryl group allows an increase in selectivity.…”
Section: Non-covalent Interaction: Brønsted Basementioning
confidence: 99%
See 1 more Smart Citation
“…Immobilization of quinine alkaloids onto polymers (styrenedivinylbenzene or acrylonitrile) allows asymmetric conjugate addition of MVK to indanone derivatives, although the selectivity is dramatically diminished. [143,144] More recently, Wu et al have reported the use of cinchona alkaloids 230 for the Michael addition of several vinyl ketones to keto-esters with good yields and enantioselectivities at room temperature (however the configuration of the stereogenic center is not reported) (Scheme 62). [145] The phenanthryl group allows an increase in selectivity.…”
Section: Non-covalent Interaction: Brønsted Basementioning
confidence: 99%
“…[142] In addition, the spatial arrangement of the tertiary amine and the hydroxy group are reported to be responsible for the selectivity,with aspecial emphasis on the hydroxy group since its acetylation causes astrong decrease in the reactivity and selectivity.T he immobilization of quinine alkaloids on polymers (styrene-divinylbenzene or acrylonitrile) allows asymmetric conjugate addition of 12 to indanone derivatives,a lthough the selectivity is dramatically diminished. [143,144] More recently,W ue tal. reported the use of cinchona alkaloids 230 for the Michael addition of several vinyl ketones to ketoesters with good yields and enantioselectivities at room temperature (however,the configuration of the stereogenic center was not reported;S cheme 62).…”
Section: Reviewsmentioning
confidence: 99%
“…Quinine (6), quinidine (7), and eucupine (8) were from commercial sources, and 0-acetylquinine (9) 9 and quinine methiodide (10) l o were synthesized according t o known procedures. Seven different catalysts were tested.…”
mentioning
confidence: 99%
“…Again, Wynberg was the first who used polymer-bound cinchona alkaloid catalysts in Michael reactions: quinine and its derivatives were immobilized by ether and ester linkages of the secondary alcohol or a quinoline alkoxy group to styrenedivinylbenzene copolymers. In the model reaction of carboxylate 5a to give indanone derivative 8a enantiomeric excesses with these catalysts did not exceed 53% [15]. Kobayashi and coworkers used the vinyl moiety of quinine for copolymerization with acrylonitrile; however, with maximum 57% ee for 8a they could not significantly improve Wynberg's results [16].…”
Section: Polymer-bound Alkaloidsmentioning
confidence: 95%